SAT0194 Significant overtreatment with biological drugs is common in routine care for patients where serum drug levels are monitored. (12th June 2018) - Perry, M. E.
Abstract : Background: Current challenges in treating rheumatic disease include using the right drug at right dose for the right length of time. Measuring serum drug levels can help prevent over- treatment, inform regarding secondary drug failure on account of immunogenicity and improve confidence to extend the interval of drug dosing. 1 This pilot work was a prelude to the implementation of the first national monitoring service worldwide within the relatively endogenous Scottish population. Objectives: 1. To develop skill and familiarity with TDM at a Scottish laboratory prior to a business case for a national service 2. To understand the reasons why a clinician would use the service as part of clinical practice 3. To understand the current extent of over and undertreatment in an endogenous population Methods: ELISA assays (Promonitor) were supplied by GRIFOLS (Barcelona) for the detection of serum levels of adalimumab (ADA), infliximab (IFX), Golimumab (GOL), Etanercept (ETA) and Rituximab (RIX). A single laboratory site was selected and laboratory training was provided. A bespoke clinical request form was developed. Adult & paediatric rheumatologists across Scotland were invited to send serum biological drug trough samples for analysis. The clinical indication for testing was also captured. Reference ranges for free drug levels and anti-drug antibody levels: Analyte: Lower limit of measurement-Upper limit of measurement. Units ug/mL: Adalimumab 0.024–12, Infliximab 0.2–14.4, Etanercept 0.035–40, Golimumab 0.036–12.8, Rituximab 0.75–204. Results: Internal calibration and quality control for the assays were established. A total of 39 IFX, 26 ADA, 14 ETA, 3 RIX, 14 GOL samples were received (total n= 96). Only 4 (4%) of patients had serum levels below the reference range and of these just one had anti drug antibodies, suggesting that immunogenicity was not a significant clinical factor in this population. Overtreatment was common:19 patients (20%) had drug levels greater than the maximum value in the reference range. 12 patients had anti-drug antibodies, but only one of these had poor disease control, suggesting a high proportion had non-neutralising antibodies. Based on this study, if all overtreated patients had dosing interval extended by 33%, this would produce a drug budget reduction of 6–7 %, easily dwarfing the setup and running costs of a biologic drug monitoring service. Clinicians requested samples to help assess flaring patients to determine if immunogenicity had occurred or drug levels were too low (n=36) confidence around tapering drug (n=28), switching to biosimilar (n=6) and miscellaneous other reasons (n=15) Conclusions: In this population, immunogenicity was not clinically relevant Overtreatment with biological drugs was common, highlighting potential longer term safety risk and opportunity for cost reduction by dose interval prolongation. Clinicians primarily indicate the usefulness of serum biological drug testing in determining if secondary failure has occurred or to aid decisions about drug dose tapering. Reference: [1]Jani, et al. Clinical Utility of Random Anti-Tumor Necrosis Factor Drug Level Testing and Measurement of Antidrug Antibodies on the Long-Term Treatment Response in Rheumatoid Arthritis. Arthritis and Rheumatology2015;67(8):2011–2019. Acknowledgements: Drs Alan Dunlop, Frank Finlay and Peter Galloway for the laborarory expertise and analysis Grifols for providing the laboratory training and assay kits Disclosure of Interest: M. Perry Grant/research support from: GRIFOLS